Estimation of Seed Production and Germination of Ficus hispida and Ficus racemosa - Ghvirly Ramadhani; Noor Farikhah Haneda; Iwan Hilwan (Department of Forestry, Faculty of Agriculture, University of Lampung, 2022)
Ficus hispida and Ficus racemosa are Moraceae species that commonly grow on riverbanks. Actions to propagate generative plants required more observation due to mutualistic symbiosis between F. hispida and F. racemosa with Ceratosolen solmsi and Ceratosolen fusciceps as pollinating insects. This study aimed to obtain data on seed production, germination, and the interaction of F. hispida and F. racemosa with pollinating insects. Research activities included seed extraction, seed germination testing, and calculation of the number of pollinating insects found in syconia. The results showed that the number of entered insects was related to syconia's receptive phase and diameter. F. hispida produced 3679 seedlings, while F. racemosa produced 2086 seedlings in one period. The number of seeds could cover a 6 ha area with a 4 m x 4 m spacing of planting. The germination percentage of F. hispida and F. racemosa was low to moderate. F. hispida seed germination was only 57.2% and F. racemosa was 68.6%. Thus, the seed should be germinated immediately after extraction. Keywords: Ficus hispida, Ficus racemosa, germination, seed production